Blood Pressure Trajectories From Childhood to Youth and Arterial Stiffness in Adulthood: A 30-Year Longitudinal Follow-Up Study - Chu, Chao; Liao, Yue-yuan; He, Ming-jun; Ma, Qiong; Zheng, Wen-ling; Yan, Yu; Hu, Jia-wen; Xu, Xian-jing; Fan, Ya-ning; Yang, Rui-hai; Mu, Jian-jun (Frontiers in Cardiovascular Medicine, 2022)
Background: This study aimed to identify the subgroups of individuals sharing similar blood pressure (BP) trajectories from childhood to youth and explore the associations of these trajectories with arterial stiffness in adulthood. Methods: A group-based trajectory model was used to identify BP trajectories among 2082 individuals in the Hanzhong adolescent hypertension cohort by using BP values repeatedly measured at four visits from childhood (6–15 years) to youth (14–23 years). The brachial–ankle pulse wave velocity (baPWV) was examined 30 years after the baseline survey. Mixed linear regression models were used to examine the associations of these trajectories with adult baPWV. Results: Among the 2082 individuals, three trajectory groups of systolic BP were identified as follows: the low-level group (n = 889), medium-level group (n = 1021), and high-level group (n = 172). The baPWV in adulthood was higher in medium-level and high-level groups compared with the low-level group (1265.3 ± 213.6 cm/s, 1349.3 ± 214.5 cm/s vs. 1198.2 ± 215.5 cm/s, all p < 0.001). After adjustment for potential confounding factors, the association between baPWV and systolic BP trajectories was statistically significant (adjusted β = 49.4 cm/s; p < 0.001 for the medium-level group and β = 107.6 cm/s; p < 0.001 for the high-level group compared with the low-level group). Similar results were obtained for the association of baPWV with the trajectories of diastolic BP and mean arterial pressure (MAP), except for pulse pressure. Conclusion: Our investigation demonstrates different BP trajectories from childhood to youth and shows the trajectories of systolic BP, diastolic BP, and MAP are significant predictors of arterial stiffness in adulthood.